Я-концепція як предмет багатоаспектного теоретизування - Фурман (Гуменюк), Оксана (Психологія і суспільство, 2018)
У статті обґрунтовується Я-концепція як системне онтогенетичне утворення внутрішнього світу людини, котре унікальне за своїми функціями, призначенням, самоорганізаційною актуалізацією, адже формує низку вагомих думок, уявлень, ставлень, знань, переживань, почуттів, мрій, розчарувань та установок про себе; вона розвивається у сімейному, а пізніше й у шкільному довкіллі, вдосконалюється у ділових та виробничих (професійних) відносинах, прогресує чи деградує у буденних стосунках упродовж життєвого шляху, є центром її соціального світу, оскільки поєднує особу з довкіллям. Висвітлюється взаємозв’язок теоретичного осмислення Я-концепції як центрального ядра самосвідомості через чотири аспекти: обґрунтування, розвитку, формування й самотворення у взаємодоповненні із методологічними підходами, що витлумачують її як гносеологічно-епістемну дійсність, онтогенетичну реальність, онтолого-феноменологічну даність та ноуменально-аксіологічну організованість. Детально аналізується психічна організація внутрішнього світу людини від Я-концепції до Ми-концепцій, де остання не є сумою окремих осіб першої, а становить якісно нову інтегральну цілісність уявлень, ставлень, установок та інших психічних утворень про колективну самосвідомість окремих груп чи групи, що здебільшого належить, наприклад, до національної самосвідомості. Водночас виявляється відмінність між трикомпонентною будовою глобальної Я-концепції Р. Бернса, котра охоплює такі складові: когнітивну (Я-образ), емоційно-оцінкову (Я-ставлення), поведінкову (Я-поведінка) та авторською чотирикомпонентною структурою позитивно-гармонійної Я-концепції (створена у 2001 році, доповнена у 2003-2006, деталізована у 2007–2018 роках), яка утримує когнітивну (Я-образ), емоційно-оцінкову (Я-ставлення), вчинково-креативну (Я-вчинок), спонтанно-духовну (Я-духовне) складові. Крім того, описуються виміри взаємопроникнення свідомості, самосвідомості та Я-концепції, котрі взаємоспричинені й становлять неподільну єдність, а також обґрунтовується авторська модель самотворення позитивно-гармонійної Я-концепції у структурі інноваційно-психологічного клімату, який не тотожний соціально-психологічному чи організаційному, а наявний у модульно-розвивальній системі навчання проф. А.В. Фурмана, що задає координати самотворення залежно від виокремлених ним: 1) періодів модульно-розвивального циклу (інформаційно-пізнавальний, нормативно-регуляційний, ціннісно-естетичний, духовний), що поширюють і збагачують соціально-культурний досвід нації та людства не тільки знаннями, уміннями, навичками, а й нормами, компетенціями, цінностями та екзистенціалами духовності, 2) послідовності психомистецьких технологій  розвивальної взаємодії у класі (проблемно-ситуативна – добування суб’єктом знань, регуляційна – нормування особистістю знань і вмінь, ціннісно-естетична –  поширення індивідуальністю здобутого культурного досвіду та компетенцій, спонтанно-духовна – самореалізація особи як універсума). Доводиться, що ідея самотворення обґрунтована нами із моделі вільного спричинення В.А. Петровського, що розвиває концепцію Я як causa sui шляхом осмислення чотирьох граней (ідеальне Я – образ, іманентне Я – інтенція, трасфінітне Я – переживання, трансцендентальне Я – думка), кожна з яких реалізує в собі одну із відомих аристотелівських причин і воднораз може бути віднесена до рангу “причини себе”. Саме ця модель слугує своєрідною відправною точкою теоретичного аналізу проблеми самотворення Я-концепції, оскільки визнання самозумовлення у психології дає змогу підтвердити достовірність не лише ідей саморуху та саморозвитку особистості, коли розвиток відбувається у внутрішньому просторі її зв’язків з іншими людьми, а й у діяльній динаміці перебігу психодуховного механізму самотворення Я через внутрішню зустріч у сфері самосвідомості вітакультурних форм активності (поведінка, діяльність, учинок, спілкування ) та “образів суб’єктивної реальності” (людина як індивід, суб’єкт, особистість, універсум, за концепцією В.І. Слободчикова, Є.І. Ісаєва).The article substantiates self-concept as a systemic ontogenetic formation of the human’s inner world, which is unique in its functions, purpose and self-organizing actualization, since it forms a number of important thoughts, ideas, attitudes, knowledge, experiences, feelings, dreams, disappointments and installations about oneself; it develops in the family, and later in the school environment, is improved in business and industrial (professional) relations, progresses or degrades in everyday relationships throughout the life course, is the center of its social world, as it combines a person with the environment. The interrelation of the theoretical comprehension of the self-concept as the central core of self-consciousness is highlighted through four aspects: substantiation, development, formation and self-creation in complementarity with methodological approaches that interpret it as epistemologically-epistemic reality, ontogenetic reality, ontological-phenomenological givens and a noumenal-axiological organization. The psychological organization of the inner world of human from the Self-concept to the We-concepts is analysed in details, where the last one is not the sum of individual persons of the first one, but is a qualitatively new integral wholeness of representations, attitudes, installations and other mental entities about the collective consciousness of individual groups or group, which in most cases belongs, for example, to national consciousness. At the same time, there is a distinction between the three-component structure of the global Self-concept of R. Burns, which encompasses the following components: cognitive (Self-image), emotional-evaluative (Self-attitude), behavioral (Self-behavior), and author’s four-component structure of positively harmonic Self-concept (created in 2001, supplemented in 2003-2006, detailed in 2007-2018), which holds cognitive (Self-image), emotional-evaluative (Self-attitude), action-creative (Self-act), spontaneously-spiritual (Self-spiritual). In addition, dimensions of interpenetration of consciousness, self-consciousness and self-concept are described, which are mutually-caused and constitute indivisible unity, and also the author’s model of self-creation of a positively harmonious Self-concept in the structure of an innovative-psychological climate is substantiated, which is not identical to a socio-psychological or organizational one, but available in the modular-developing training system of prof. A. V. Furman, who specifies the coordinates of self-creation, depending on the ones he has singled out: 1) the periods of the modular-developing cycle (information-cognitive, normative-regulatory, value-aesthetic, spiritual), which extend and enrich the socio-cultural experience of the nation and humanity, not only with knowledge, skills, abilities, but also norms, competencies, values and development of spirituality, 2) the sequence of psycho-artistic technologies of developmental interaction in the classroom (problem-situational – the acquisition of knowledge by the subject, regulatory – the rationing of knowledge and skills by the personality, value-aesthetic - the spread of the acquired cultural experience and competences by the individuality, spontaneously-spiritual – self-realization of the person as a universe). It is proved that the idea of self-formation is substantiated by us from the model of free causing of V. A. Pertrovskiy, who develops the concept of Self as causa sui through the comprehension of the four facets (ideal Self-image, immanent Self-intention, tranfinite Self-experience, transcendental Self-thought), each of which implements in itself one of the known Aristotelian causes and can simultaneously be attributed to the rank “cause of yourself”. Namely this model is a peculiar starting point for the theoretical analysis of the self-creation problem of Self-concept, since the recognition of self-assertion in psychology makes it possible to confirm the authenticity of not only the ideas of self-movement and self-development of the personality, when development takes place in the internal space of its connections with other people, but also in the active dynamics of the psychological mechanism course of self-creation of Self through an internal meeting in the sphere of self-consciousness of vita-cultural forms of activity (behavior, activity, deed, communication) and “images of the subjective reality” (human as an individual, a subject, a personality, a universum, according to the concept of V. I. Slobodchikov, E. I. Isaev).